Направления и результаты селекции овощного перца для условий Приднестровья и Российской Федерации - Тимина, О.О.; Тимин, О.Ю.; Томлекова, Н.; Валчев, Н.Ю. (Фактори експериментальної еволюції організмів, 2013)
Aims. The objective of our research was the creation of new varieties and hybrids of vegetable pepper with the complex of economically-valuable traits adequate to modern requirements of culture. Methods. The creation of varieties and hybrids F1 was conducted using crosses backcrosses and recurrent selection with best identified donors with complex economically-valuable traits including mutant gene pool. Seed production of hybrids was developed on fertile and sterile background. Results. Breeding and genetic monitoring of Capsicum gene pool resulted in new varieties and hybrids with the given parameters. Conclusions. Five varieties and two hybrids have been developed with a complex of economically-valuable traits adequate to modern requirements of culture.

Key words: Capsicum annuum var. annuum, gene pool, economically-valuable traits, breeding and genetic monitoring, varieties, hybrids.